Investigation of development of discharge in nanosecond range under atmospheric conditions; Proceedings of the Xth International Conference on Phenomena in Ionized Gases, Oxford, september 13-18, 1971; Pt. 1 - Bichkov Ju. I.; Gavrilyuk P. A.; Korolev Yu. D.; Mesyats G. A. Gennady Andreyevich (1971, 1971)
В фонде НТБ ТПУ отсутствует